Maritime History as Global History. - Fusaro, Maria (Research in Maritime History LUP., 2017)
This study aims to provide new insights into the connections between maritime history and global history. It demonstrates the significance of maritime activity as a conduit of global exchange by examining local, national, and international interdependencies and trade networks, and a broad range of time periods, geographical areas, and various sub-divisions of maritime historical research.